2006
DOI: 10.1016/j.virol.2005.12.025
|View full text |Cite
|
Sign up to set email alerts
|

A single amino acid substitution within the transmembrane domain of the human immunodeficiency virus type 1 Vpu protein renders simian–human immunodeficiency virus (SHIVKU-1bMC33) susceptible to rimantadine

Abstract: Previous studies from our laboratory have shown that the transmembrane domain (TM) of the Vpu protein of human immunodeficiency virus type 1 (HIV-1) contributes to the pathogenesis of SHIV(KU-1bMC33) in macaques and that the TM domain of Vpu could be replaced with the M2 protein viroporin from influenza A virus. Recently, we showed that the replacement of the TM domain of Vpu with that of the M2 protein of influenza A virus resulted in a virus (SHIV(M2)) that was sensitive to rimantadine [Hout, D.R., Gomez, M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 47 publications
3
29
0
Order By: Relevance
“…Since scrambling the TM domain blocks both ion channel activity and efficient virus release, it was thought that these activities were related (10,57). Indeed, amiloride-based drugs that block Vpu channel function have been shown to display antiviral activity against HIV-1 in (tetherin-positive) macrophages (9), and other studies report that chimeric Vpu proteins bearing the TM domain of the influenza A virus proton channel M2 were functional for virus release and sensitive to rimantadine (19,20). However, since we found that mutation of S23, known to be required for channel activity (60) and the potential target for amilorides (26), had no effect on tetherin inactivation in our assays, there appears to be a discrepancy in directly correlating cation transport and virus release (tetherin antagonism).…”
Section: Discussionmentioning
confidence: 99%
“…Since scrambling the TM domain blocks both ion channel activity and efficient virus release, it was thought that these activities were related (10,57). Indeed, amiloride-based drugs that block Vpu channel function have been shown to display antiviral activity against HIV-1 in (tetherin-positive) macrophages (9), and other studies report that chimeric Vpu proteins bearing the TM domain of the influenza A virus proton channel M2 were functional for virus release and sensitive to rimantadine (19,20). However, since we found that mutation of S23, known to be required for channel activity (60) and the potential target for amilorides (26), had no effect on tetherin inactivation in our assays, there appears to be a discrepancy in directly correlating cation transport and virus release (tetherin antagonism).…”
Section: Discussionmentioning
confidence: 99%
“…If one compares the sequence of the Vpu and M2 TMDs, the subtype B Vpu contains the sequence Ala-X-X-X-Trp in approximately the same position as M2 with the tryptophan being invariant in Vpu [50]. We subsequently showed that substitution of the alanine in this motif with a histidine residue resulted in a SHIV (SHIV VpuA19H ) that became more sensitive to rimantadine than the SHIV M2 virus [35]. These results indicate that a single amino acid substitution within the TMD of the Vpu protein converts a rimantadine-resistant SHIV to a rimantadine-sensitive SHIV.…”
Section: Is Vpu An Ion Channel Protein?mentioning
confidence: 99%
“…SIV cpz CAM13, SIV cpz ANT, and SIV cpz TAN1 only contain a single casein kinase II site. All four vpu isolates were fused in frame to the gene for enhanced green fluorescence protein (EGFP) and expressed under the control of a CMV promoter, similar to the HIV-1 subtype B vpu genes our laboratory has previously analyzed [34, 35, 74]. All four SIV cpz Vpu fusion proteins were membrane-associated, partially co-localized with DsRed-ER and ECFP-Golgi marker proteins, and completely co-localized with an ECFP-Membrane marker.…”
Section: The Cd4 Down-modulation Function Is Conserved In Vpu Proteinmentioning
confidence: 99%
“…Park et al [27] determined the three-dimensional structure of the channel-forming trans-membrane domain (VpuTM). Substitution of alanine at position 18 by a histidine (A18H) has been shown to render HIV-1 infections susceptible to rimantadine [28]. The structure of A18H VpuTM was determined, and compared to that of wild-type Vpu TM [29].…”
Section: Vpu From Hiv-1mentioning
confidence: 99%